Developing a risk control modifying matrix in assessing occupational stress in port terminal - Yaakub, Norwahida; Elias, Saliza; Zainuddin, Huda; Mohd Noor, Mohd Azhar; Baharudin, Mohd Rafee (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Occupational stress is a universal phenomenon which lead to increase the adverse health effect, performance and general well-being of a worker. These problems need to be assess using a suitable risk assessment matrix. Current method available does not integrate the element of existing risk control measures. In this study, port terminal was chosen as a workplace due to its heavy daily operations.Based on the safety and health data available, a framework of this new proposed matrix was then developed accordingly.Thus, this paper explained the overall process of the development on Occupational Stress Risk Assessment Matrix (OSRAM) which emphasize on a risk control modifying matrix in the port terminal